Depression and Employment Status in Primary and Tertiary Care Settings. (January 2015) - Rizvi, Sakina J; Cyriac, Anna; Grima, Etienne; Tan, Mary; Lin, Peter; Gallaugher, Laura Ashley; McIntyre, Roger S; Kennedy, Sidney H
Objective: Major depressive disorder (MDD) is a leading cause of disability. Impairment in work function considerably adds to symptom burden and increases the economic impact of this disorder. Our study aimed to investigate the factors associated with work status in MDD within primary and tertiary care. Method: We used data from 2 large databases for our analysis—Study 1: the InSight database, a chart review of MDD patients treated by primary care physicians across Canada ( n = 986); and Study 2: the International Mood Disorders Collaborative Project, a cross-sectional study of mood disorder patients (Canadian data only: n = 274). Results: Both studies demonstrated high rates of unemployment and disability (30.3% to 42.1%). Quebec showed the highest rate of unemployment (21%) and British Columbia had the greatest percentage of patients on disability (15%). Employed and unemployed groups were similar based on clinical characteristics; however, unemployed people may have higher age, prevalence of medical comorbidity, and greater likelihood of receiving a benzodiazepine. Increased disability rates were associated with history of childhood abuse, duration of current major depressive episode, comorbidity, benzodiazepine use, as well as greater depression and anxiety severity. The unemployed–disability groups had greater somatic symptoms and anhedonia. In keeping with this, anhedonia was the strongest predictor of disability. Absenteeism was also high across both studies. Conclusions: Unemployment and disability rates in MDD are high. The presence of anhedonia and medical comorbidity significantly influenced work status, emphasizing the need for treatment strategies to alleviate the additional symptom burden in this subpopulation.